Accelerating Digital Transformation during the COVID-19 Pandemic: A Model Design for Indonesian MSMEs - Mercurius Broto Legowo; Fangky Antoneus Sorongan (Binus Business Review, 2022)
The acceleration of digital transformation and business model innovationsÂ fundamentally improves business growth and performance. However, the occurrence of the COVID-19 pandemic has a significant influence on the insecurity of many business actors, especially Micro Small Medium Enterprises (MSMEs). There are many efforts to recover the national economy by accelerating digital transformation for MSMEs programs by the government of the Republic of Indonesia. However, the problem arises when the process of accelerating digital transformation in Indonesian MSMEs is considered slow to encourage Indonesiaâ€™s National Economic Recovery (PEN as shortened in Indonesian) during the COVID-19 pandemic. The research aimed to present a design model for accelerating digital transformation during the COVID-19 pandemic for Indonesian MSMEs. The research applied a descriptive-analytic approach with a qualitative method. Then, the analysis reviewed the content analysis of previous research. The two research models were analyzed. One was from Indonesia, while another one was from outside Indonesia. The results of the model design reveal that the acceleration of digital transformation is influenced by business driving factors and impacts the gaining value from business model innovations. The model of accelerating digital transformation for MSMEs is expected to contribute significantly to supporting government programs and strengthening National Economic Recovery policies during the COVID-19 pandemic.